Glaucoma epidemiology in the Russian Federation - V. V. Neroev; L. A. Mikhaylova; T. N. Malishevskaya; S. Yu. Petrov; O. M. Filippova (Российский офтальмологический журнал, 2024)
Glaucoma is worldwide the most common cause of irreversible blindness. Its prevalence in the population older than 40 years is about 3.5 %, and correlates with age. The most common type is primary open-angle glaucoma (POAG). The global prevalence of POAG is expected to grow from 76.0 million in 2020 to 111.8 million by 2040. In 2022, a total of 1,250,558 patients with glaucoma were registered in the Russian Federation, of which 110,680 had newly diagnosed glaucoma. The overall glaucoma incidence rate in Russia shows a steady growth: in 2022, it increased by 30 % as compared to 2013. In order to meet the challenge, medical care of glaucomatous patients is on the rise: the contingent receiving dispensary observation increased by 6.8 % over the last 10 years,  whilst surgical treatment involved 28.1 % more patients.